DIGITAL HUMOR AND ITS IMPACT ON ADOLESCENT LITERACY: A LOOK AT HIGH SCHOOL READING TRENDS - Ayu, Citra; Rizky, Ramanda; Herdi, Herdi (English Review: Journal of English Education, 2024)
Reading is a critical skill that contributes significantly to academic success and personal growth, especially at the High School level. Therefore, this study explores the relationship between Reading Motivation, Reading Comprehension, and Online Humorous Reading Content among high school pupils. Leveraging a correlational design and quantitative research methods, data was collected from 186 eleventh grade pupils through questionnaires and tests. Statistical analysis, including Moderated Regression Analysis (MRA), was used to test the relationship between variables. Findings showed a significant effect of Reading Motivation on Reading Comprehension, with Online Humorous Reading Content as a moderating variable since the acceptance of alternate hypotheses (Ha) had been obtained. Specifically, Online Humorous Reading Content was found to increase pupils’ interest in reading and reduce barriers to reading comprehension, thus improving overall reading performance. This study underscores the importance of incorporating entertaining reading materials into the curriculum to foster engagement and improve learning outcomes. Undeniably, these findings contribute valuable insights for educators aiming to improve reading skills and create a stimulating learning environment in high school settings.